Hábitos alimentarios y su influencia en el sobrepeso y obesidad en escolares del Centro de Salud Alfredo Baquerizo Moreno del Cantón Jujan, Guayas del periodo mayo - septiembre 2019 - Joutex Jow, Jummy Julyn (2019)
Introduction: According to the world health organization, the alarming increase in overweight and obesity worldwide, together with the consequences on the physical (nutritional) and psychological health of the population, has given us the purpose of conducting a thorough investigation in schoolchildren from 5 to 11 years of the Alfredo Baquerizo Moreno Jujan health center to identify how eating habits influence the development of the same diseases and the impact they will have in the future. Objective: To identify eating habits and their influence on overweight and obesity in schoolchildren of the Alfredo Baquerizo Moreno health center of the Jujan canton, Guayas, from May - September 2019. Methodology: This research project has a quantitative modality, the type of investigation of this project was field, descriptive and cross-sectional, with a probability sampling of 90% reliability, leaving 100 schoolchildren from the Alfredo Baquerizo Moreno health center in the canton Jujan. Results: Of the total of 100 schoolchildren, 30% consume artificial juices every day, 35% sweet every day, 2% ice cream once a week, 2% cachitos, tostitos and doritos 3 times a week, 28% salchipapas every day and 3% hamburgers 2 times a week. We can see that there is a higher frequency of consumption of sweets, followed by artificial juices and salchipapas every day, also in the nutritional assessment, 49% have a body mass index for normal age within p50, while 42% has> p85 classifying them with overweight and 9%> p95 classifying them with obesity. Conclusions: The objectives were satisfactorily fulfilled and the influence of eating habits on overweight and obesity of schoolchildren at the Alfredo Baquerizo Moreno health center in Jujan canton was identified.